CASE STUDY ON MOBILE APPLICATION CODES AND FAILURES - Serafini, Luis Fernando; Carleto, Nivaldo (Revista Interface Tecnológica, 2024)
The aim of this case study was to develop a mobile application to help maintainers make daily decisions, using data collected through surveys of specific groups. The methodology adopted was a quantitative approach, using questionnaires via WhatsApp and Telegram. The survey forms were distributed to selected groups, and the responses were collected and transformed into data, forming the basis of a case study. Through quantitative analysis of these responses, it was possible to identify the needs and validate the idea of the app. The main results indicated that the majority of participants approved of the idea, providing valuable information for the development of the application. The survey showed that there is a significant demand for a tool to help maintainers with their daily decisions. Based on this data, the development of the application began, and it became clear that the efforts will be recognized in the market. In conclusion, the study provided a solid basis for the creation of the application, showing the importance of an approach based on quantitative data to guarantee the validity and relevance of the proposed solution.